The Epidemiology of Breast Implant–Associated Anaplastic Large Cell Lymphoma in Australia and New Zealand Confirms the Highest Risk for Grade 4 Surface Breast Implants. Issue 5 (May 2019) - Magnusson, Mark; Beath, Kenneth; Cooter, Rodney; Locke, Michelle; Prince, H. Miles; Elder, Elisabeth; Deva, Anand K.
Abstract : Background: The epidemiology and implant-specific risk for breast implant–associated (BIA) anaplastic large cell lymphoma (ALCL) has been previously reported for Australia and New Zealand. The authors now present updated data and risk assessment since their last report. Methods: New cases in Australia and New Zealand were identified and analyzed. Updated sales data from three leading breast implant manufacturers (i.e., Mentor, Allergan, and Silimed) were secured to estimate implant-specific risk. Results: A total of 26 new cases of BIA-ALCL were diagnosed between January of 2017 and April of 2018, increasing the total number of confirmed cases in Australia and New Zealand to 81. This represents a 47 percent increase in the number of reported cases over this period. The mean age and time to development remain unchanged. The implant-specific risk has increased for Silimed polyurethane (23.4 times higher) compared with Biocell, which has remained relatively static (16.5 times higher) compared with Siltex implants. Conclusions: The number of confirmed cases of BIA-ALCL in Australia and New Zealand continues to rise. The implant-specific risk has now changed to reflect a strong link to implant surface area/roughness as a major association with this cancer. Abstract : Patient Safety CME.